Probiotics supplementation for athletes - Clinical and physiological effects - Pyne, D. B.; West, N. P.; Cox, A. J.; Cripps, A. W. (European Journal of Sport Science, 2015)
Probiotic supplementation has traditionally focused on gut health. However, in recent years, the clinical applications of probiotics have broadened to allergic, metabolic, inflammatory, gastrointestinal and respiratory conditions. Gastrointestinal health is important for regulating adaptation to exercise and physical activity. Symptoms such as nausea, bloating, cramping, pain, diarrhoea and bleeding occur in some athletes, particularly during prolonged exhaustive events. Several studies conducted since 2006 examining probiotic supplementation in athletes or highly active individuals indicate modest clinical benefits in terms of reduced frequency, severity and/or duration of respiratory and gastrointestinal illness. The likely mechanisms of action for probiotics include direct interaction with the gut microbiota, interaction with the mucosal immune system and immune signalling to a variety of organs and systems. Practical issues to consider include medical and dietary screening of athletes, sourcing of recommended probiotics and formulations, dose-response requirements for different probiotic strains, storage, handling and transport of supplements and timing of supplementation in relation to travel and competition.